2021
DOI: 10.1016/j.jcf.2020.11.014
|View full text |Cite
|
Sign up to set email alerts
|

CFTR plays an important role in the regulation of vascular resistance and high-fructose/salt-diet induced hypertension in mice

Abstract: Background:The pathophysiological roles of cystic fibrosis transmembrane-conductance regulator (CFTR) Cl − channels in the regulation of blood pressure (BP) remain controversial. Here we studied the function of CFTR Cl − channels in regulation of BP and in the high-fructose-salt-diet (HFSD) induced hypertension in mice. Methods:The systolic, diastolic and mean BP (SBP, DBP and MBP, respectively) were continuously monitored from unrestricted conscious wild-type ( cf tr + / + ) FVB and CFTR -knockout ( cf tr −/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In previous study, average SBP and DBP of 24hour, daytime and night time of Cftr −/− mice were all significantly higher than those of Cftr +/+ mice, however, Cftr knockout did not alter SBP or DBP recorded from 4:00 PM to 8:00 PM [12]. To investigate whether CFTR play a part in Ang II induced hypertension, Cftr +/+ and Cftr −/− mice were used to establish Ang II infusion induced hypertension model, SBP and DBP was measured at 6:00 PM 0, 3, 6, 9, 12 and 14 days after the pumps were implanted.…”
Section: Cftr Participates In the Progress Of Ang II Induced Hypertensionmentioning
confidence: 69%
See 3 more Smart Citations
“…In previous study, average SBP and DBP of 24hour, daytime and night time of Cftr −/− mice were all significantly higher than those of Cftr +/+ mice, however, Cftr knockout did not alter SBP or DBP recorded from 4:00 PM to 8:00 PM [12]. To investigate whether CFTR play a part in Ang II induced hypertension, Cftr +/+ and Cftr −/− mice were used to establish Ang II infusion induced hypertension model, SBP and DBP was measured at 6:00 PM 0, 3, 6, 9, 12 and 14 days after the pumps were implanted.…”
Section: Cftr Participates In the Progress Of Ang II Induced Hypertensionmentioning
confidence: 69%
“…Moreover, Cftr knockout enhanced Ang II induced BP elevation during the development of hypertension, without altering BP in normotensive mice. Previous study indicated that CFTR might play a little role in circadian regulation of BP [12]. Both Cftr −/− and Cftr +/+ mice displayed a bimodal circadian pattern over 24-hour period but BP peaks of Cftr −/− mice were higher and later when compared to Cftr +/+ mice.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…CFTR (CF transmembrane conductance regulator) [380], RHOB (ras homolog family member B) [396], LMNA (lamin A/C) [388], HGF (hepatocyte growth factor) [371], CCL5 [360] and NGFR (nerve growth factor receptor) [383] were altered expression in the Alzheimer’s Disease. CFTR (CF transmembrane conductance regulator) [551], LMNA (lamin A/C) [558], ERBB3 [331], HGF (hepatocyte growth factor) [494], CCL5 [540] and NGFR (nerve growth factor receptor) [554] have been demonstrated to accelerate hypertension progression. LMNA (lamin A/C) [222], HGF (hepatocyte growth factor) [212] and NGFR (nerve growth factor receptor) [220] expression migh be regarded as an indicator of susceptibility of amyotrophic lateral sclerosis.…”
Section: Discussionmentioning
confidence: 99%